A virtual lab for modeling and control of a solar collector field. Issue 2 (2020) - Guzmán, J.L.; Berenguel, M.; Merchan, A.; Gil, J.D.; Álvarez, J.D.
Abstract: Research and teaching on renewable energies are very important topics worldwide. Most of the renewable energy processes are quite complex to analyze and to study. For that reason, educational resources as support for the teaching and learning of these processes dynamics are very useful. Thus, this paper presents a virtual lab as support to the modeling and control concepts of a solar collector field, as these kind of solar plants are widely used at industrial level requiring control skills. This interactive tool is used as part of several subjects in a Master on Solar Energy at the University of Almería, Spain. Examples about open and closed-loop exercises are presented.